Diversifying Arena of Drug Synthesis: In the Realm of Lipase Mediated Waves of Biocatalysis - Sahil Verma (MDPI AG, 2021)
Hydrolases, being most prominent enzymes used in industrial processes have left no stone unturned in fascinating the pharmaceutical industry. Lipases, being a part of acyl hydrolases are the ones that function similarly to esterases (except an interfacial action) wherein they generally catalyze the hydrolysis of ester bonds. Be it in terms of stereoselectivity or regioselectivity, lipases have manifested their promiscuous proficiency in rendering biocatalytic drug synthesis and intermediates thereof. Industrial utilization of lipases is prevalent since decades ago, but their distinctive catalytic competencies have rendered them suitable for maneuverability in various tides of biocatalytic industrial process development. Numbers of exquisite catalysts have been fabricated out of lipases using nanobiotechnology whereby enzyme reusability and robustness have been conferred to many of the organic synthesis procedures. This marks a considerable achievement of lipases in the second wave of biocatalysis. Furthermore, in the third wave an advent of genetic engineering has fostered an era of customized lipases for suitable needs. Be it stability or an enhanced efficacy, genetic engineering techniques have ushered an avenue for biocatalytic development of drugs and drug intermediates through greener processes using lipases. Even in the forthcoming concept of co-modular catalytic systems, lipases may be the frontiers because of their astonishing capability to act along with other enzymes. The concept may render feasibility in the development of cascade reactions in organic synthesis. An upcoming wave demands fulfilling the vision of tailored lipase whilst a far-flung exploration needs to be unveiled for various research impediments in rendering lipase as a custom fit biocatalyst in pharmaceutical industry.